2015
DOI: 10.1175/jhm-d-14-0237.1
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Nature of Extreme Hydrological Events in the Northeastern United States

Abstract: Recent analyses of extreme hydrological events across the United States, including those summarized in the recent U.S. Third National Climate Assessment (May 2014), show that extremely large (extreme) precipitation and streamflow events are increasing over much of the country, with particularly steep trends over the northeastern United States. The authors demonstrate that the increase in extreme hydrological events over the northeastern United States is primarily a warm season phenomenon and is caused more by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 39 publications
5
69
0
Order By: Relevance
“…However, there is an increased frequency of floods in the warm season (Jun–Oct)—historically flood‐poor months at nearly all gages (Figures and ). This trend generally matches the seasonality of regional upward trends in precipitation totals, extremes, and persistence (Frei et al, ; Guilbert, Betts, Rizzo, Beckage, & Bomblies, ; Huang, Winter, & Osterberg, ; Huang, Winter, Osterberg, Horton, & Beckage, ), indicating flooding is becoming more likely during a time of year when evapotranspiration and antecedent soil moisture conditions have historically not favoured flooding (Ivancic & Shaw, ). The increase in Jun–Oct flood counts also supports the findings of Frei et al () who found warm season high streamflow in the Northeast has increased in frequency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is an increased frequency of floods in the warm season (Jun–Oct)—historically flood‐poor months at nearly all gages (Figures and ). This trend generally matches the seasonality of regional upward trends in precipitation totals, extremes, and persistence (Frei et al, ; Guilbert, Betts, Rizzo, Beckage, & Bomblies, ; Huang, Winter, & Osterberg, ; Huang, Winter, Osterberg, Horton, & Beckage, ), indicating flooding is becoming more likely during a time of year when evapotranspiration and antecedent soil moisture conditions have historically not favoured flooding (Ivancic & Shaw, ). The increase in Jun–Oct flood counts also supports the findings of Frei et al () who found warm season high streamflow in the Northeast has increased in frequency.…”
Section: Discussionmentioning
confidence: 99%
“…This trend generally matches the seasonality of regional upward trends in precipitation totals, extremes, and persistence (Frei et al, ; Guilbert, Betts, Rizzo, Beckage, & Bomblies, ; Huang, Winter, & Osterberg, ; Huang, Winter, Osterberg, Horton, & Beckage, ), indicating flooding is becoming more likely during a time of year when evapotranspiration and antecedent soil moisture conditions have historically not favoured flooding (Ivancic & Shaw, ). The increase in Jun–Oct flood counts also supports the findings of Frei et al () who found warm season high streamflow in the Northeast has increased in frequency. Interestingly, Mallakpour and Villarini () showed an increased frequency of summer floods in the eastern part of the central United States—an area proximal to the Northeast United States that has a similar climate and where the summer season has historically been a minor contributor to flood occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations